2020
DOI: 10.1089/fpd.2019.2778
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Season, Processing Plant, and Hide Cleanliness Scores with Prevalence and Concentration of Major Shiga Toxin–Producing Escherichia coli on Beef Cattle Hides

Abstract: The objectives of this study were (1) to estimate the prevalence and concentration of the seven major Shiga toxin-producing Escherichia coli (STEC) serogroups (O26, O45, O103, O111, O121, O145, and O157), collectively called STEC-7, on cattle hides collected in different seasons and beef processing plants; and (2) to determine associations of season, plant, and hide cleanliness scores with the prevalence and concentration of STEC-7. A total of 720 hide surface samples (240/season) were collected over three sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In contrast, testing methods in five studies involved determining the virulence profiles of isolated colonies first before then determining the serotypes only of those colonies that tested positive for stx genes (and sometimes other virulence factors) (methods I–M in Table 1; Ballem et al, 2020; Engelen et al, 2020b; Ekiri et al, 2014; Mellor et al, 2016; Pearce et al, 2004). A third variation of this process, reported in four studies, was the simultaneous characterization of isolates’ serotype and virulence profiles, whereby the virulence profile of an isolate was determined regardless of its serotype (or vice versa) (methods N–P in Table 1; Cull et al, 2017; Cernicchiaro et al, 2020; Dewsbury et al, 2015; Paddock et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, testing methods in five studies involved determining the virulence profiles of isolated colonies first before then determining the serotypes only of those colonies that tested positive for stx genes (and sometimes other virulence factors) (methods I–M in Table 1; Ballem et al, 2020; Engelen et al, 2020b; Ekiri et al, 2014; Mellor et al, 2016; Pearce et al, 2004). A third variation of this process, reported in four studies, was the simultaneous characterization of isolates’ serotype and virulence profiles, whereby the virulence profile of an isolate was determined regardless of its serotype (or vice versa) (methods N–P in Table 1; Cull et al, 2017; Cernicchiaro et al, 2020; Dewsbury et al, 2015; Paddock et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to variation in the sequence of pathogen characterization, the methods for E. coli isolation when used were not standard across studies. Some always subjected enriched samples to immunomagnetic separation (IMS) prior to plating on growth media (methods A–C, J–K, and O–R in Table 1; e.g., Cernicchiaro et al, 2014, 2020; Dewsbury et al, 2015; Ekiri et al, 2014; Irshad et al, 2017; Hallewell et al, 2016; Pearce et al, 2004; Paddock et al, 2014; Sasaki et al, 2013; Schneider, Klopfenstein, et al, 2018; Stanford et al, 2017; Schneider, Lewis, et al, 2018; Stanford et al, 2016) while others did not or, in the case of Jaros et al (2016), only when target serotypes were not isolated when sample enrichments were first incubated without the use of IMS. When used, the types and manufacturers of the IMS beads themselves were variable between studies, and a variety of growth media and specific incubation conditions were reported across all studies that attempted isolation of bacterial colonies.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to electronic databases, we hand searched reference lists of peerreviewed papers and 17 articles were identified in the hand search that were not found in the electronic search. By limiting this review to only consider peer-reviewed literature, we were not able to include data that were not yet published at the time of our search (March 2019) but were pertinent to our research question such as Cernicchiaro et al (2020) and other studies discussed internally and/or at conferences but not yet published. While this limited our sample size of eligible articles, the articles that were included in this review underwent a rigorous peer-review process and are more likely representative of final, accurate estimates, which may or may not be the case for preliminary data shared at conferences.…”
Section: Limitations Of the Reviewmentioning
confidence: 99%
“…Whereas the seasonality of the top 6 has been recently evaluated (Ekiri et al, 2014;Dewsbury et al, 2015;Schneider et al, 2018a), the limited number of studies precluded us from evaluating season in this review. Recently, our group (Cernicchiaro et al, 2020) published a study evaluating associations between season, processing plants, and hide cleanliness scores with prevalence and concentration on beef cattle hides in the USA for non-O157 STEC. This research demonstrated the seasonality of non-O157 STEC, by O group, as well as differences observed between plants and with quantification data on cattle hides presented.…”
Section: Limitations Of the Reviewmentioning
confidence: 99%